Probing binding specificity of the sucrose transporter AtSUC2 with fluorescent coumarin glucosides. (1st March 2018) - De Moliner, Fabio; Knox, Kirsten; Reinders, Anke; Ward, John M; McLaughlin, Paul J; Oparka, Karl; Vendrell, Marc
Abstract : Natural and synthetic fluorescent coumarin glucosides were used as probes to analyze the key structural features that enable recognition and transport by the Arabidopsis sucrose transporter AtSUC2. Abstract: The phloem sucrose transporter, AtSUC2, is promiscuous with respect to substrate recognition, transporting a range of glucosides in addition to sucrose, including naturally occurring coumarin glucosides. We used the inherent fluorescence of coumarin glucosides to probe the specificity of AtSUC2 for its substrates, and determined the structure–activity relationships that confer phloem transport in vivo using Arabidopsis seedlings. In addition to natural coumarin glucosides, we synthesized new compounds to identify key structural features that specify recognition by AtSUC2. Our analysis of the structure–activity relationship revealed that the presence of a free hydroxyl group on the coumarin moiety is essential for binding by AtSUC2 and subsequent phloem mobility. Structural modeling of the AtSUC2 substrate-binding pocket explains some important structural requirements for the interaction of coumarin glucosides with the AtSUC2 transporter.